Preparation of Curcuma xanthorrizha Roxb. with pressure blanching on the antioxidant activity and preference level of cookies - Dwiyati pujimulyani; Bayu Kanetro; Audrey Amira Crystalia; Sulkhan Windrayahya; Dian Ayu Rahmasari (jurnal1, 2025)
Curcuma xanthorrizha Roxb. (CX) contains curcuminoids which are natural antioxidants to fight free radicals. Blanching can increase the antioxidant activity of a product. One blanching method is pressure blanching using an autoclave. The type of solvent determines the antioxidants extracted in a food. The purpose of this study was to determine the appropriate time to maintain the bioactive compounds in CX from the appropriate blanching for the preparation of cookies with the addition of CX powder. This study used a two factorial Completely Randomised Design (CRD), namely the length of time of pressure blanching (0, 2.5, 5, 7.5 and 10 min) and the type of solvent (80% methanol, 80% ethanol, and 80% acetone) for CX powder and the best results were used to make CX cookies with variation of selected CX powder (1.5, 3 and 4.5 g) and baking temperature (130, 140 and 150 °C). The results showed that CX powder with a pressure blanching time of 5 min had the highest antioxidant activity 2,2-diphenyl-1-picrylhidrazyl (DPPH), antioxidant activity Ferric Reducing Antioxidant Power (FRAP), total phenol content (TPC), flavonoids, β-carotene and condensed tannins. The addition of CX powder and variations in baking temperature had a significant effect on the chemical properties, and the preference level of the cookies produced. The selected cookies product is the addition of 1.5 g CX powder and baking temperature of 130 °C which has a moisture content of 3.17%, protein content of 10.81%, DPPH antioxidant activity of 32.10% RSA, TPC 9.08 mg GAE/g, and total flavonoids 0.61 mg QE/g.